The Meaning of Tadzkir and Ta'nits From A Linguistic Perspective Al-Quran - Wahyuni, Indah; Sofyan Hadi (Journal of Practice Learning and Educational Development, 2026)
This study discusses the meaning of tadzkir and ta'nīts in the linguistic perspective of the Qur'an using a qualitative approach through literature study. Data were obtained from verses of the Qur'an, tafsir books, Arabic linguistic literature, and related studies. Analysis was conducted using content analysis to identify the forms of tadzkir and ta'nīts as well as their semantic and rhetorical functions. The results show that the use of tadzkir and ta'nīts in the Qur'an not only follows grammatical rules but also contains contextual meanings that reinforce the message of the verse. The mudzakkar form tends to emphasize the meaning of strength and breadth of generalization, while the mu'annats form is used to indicate specificity of meaning and depth of context. In conclusion, the choice of masculine and feminine forms in the Qur'an is part of the beauty of language that is important in the interpretation of verses.